1989
DOI: 10.1007/bfb0017966
|View full text |Cite
|
Sign up to set email alerts
|

Thermotropic Mesophases in Element-Organic Polymers

Abstract: This review is primarily concerned with mesomorphic behaviour of element-organic polymers, such as linear and cyclolinear polyorganosiloxanes and linear polyphosphazenes. These polymers can form thermotropic mesophases without any mesogens. Recent development in thermodynamics, kinetics, structure and morphology, elasticity and thermoelasticity and some other properties are considered. The influence of the molecular structure and molecular weight of linear macromolecules on the ability to form the mesophases a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0
2

Year Published

1992
1992
2017
2017

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 95 publications
(48 citation statements)
references
References 70 publications
2
44
0
2
Order By: Relevance
“…These mesophases, named as condis-crystal or hexagonal columnar mesophase, are partly disordered crystalline modifications in thermodynanic equilibrium. They are formed by parallel packed macromolecules in extended macroconformation, main and side chains being conformationally disordered [3,4]. Similar types of mesophases were observed in some linear and cyclolinear polyorganosiloxanes [3,4].…”
Section: Introductionmentioning
confidence: 65%
See 1 more Smart Citation
“…These mesophases, named as condis-crystal or hexagonal columnar mesophase, are partly disordered crystalline modifications in thermodynanic equilibrium. They are formed by parallel packed macromolecules in extended macroconformation, main and side chains being conformationally disordered [3,4]. Similar types of mesophases were observed in some linear and cyclolinear polyorganosiloxanes [3,4].…”
Section: Introductionmentioning
confidence: 65%
“…The phase behavior in bulk of poly[bis-(2,2,3,3-tetrafluoropropoxy)phosphazene] (PFP-C3), poly[bis-(2,2,3,3,4,4,5,5-octafluoropentoxy)phosphazene] (PFP-C5) and poly[bis- (2,2,3,3,4,4,5,5,6,6,7,7-dodecafluoroheptoxy)phosphazene] (PFP-C7) was studied in Refs. 5 and 6, which was shown to be determined by an interplay between the packing of macromolecules on the whole and the registering of side groups.…”
Section: Introductionmentioning
confidence: 99%
“…As a result, mesogenic properties are closely coupled with the polymeric properties. Considering the fact that the polymer chain conformation is dominated by the conformation of the flexible spacer, an alteration of the flexible group may influence the molecular packing into a mesophase and thereby resulting in a structure and properties that will depart from those of the low molecular weight mesogens (Godovsky et al 1989). A number of liquid crystalline main chain polymers, such as: polyesters ( Fig.…”
Section: Main Chain Liquid Crystalline Polymersmentioning
confidence: 99%
“…[1][2][3][4] Furthermore, these polymers disAn investigation of random copoly(di-n-alkylsiplay both a low-temperature as well as a highloxane/di-n-hexylsiloxane)s has shown that structemperature crystalline modification. In the lowtural irregularities have a profound influence on temperature crystal the siloxane chains are rigidly the stability of the mesophase.…”
Section: Introductionmentioning
confidence: 98%